Experience of Managing Countertransference Through Self-Guided Imagery in Meditation Among Healthcare Professionals - Aasan, Olaug Julie; Brataas, Hildfrid Vikkelsmo; Nordtug, Bente (Frontiers in Psychiatry, 2022)
Introduction As a part of the therapeutic relationship, a significant, well-established predictor of outcomes in psychiatric healthcare, healthcare professionals' emotional reactions to patients may affect treatment outcomes. Aim The aim of our study was to explore and describe healthcare professionals' experiences with managing countertransference using skills from a training program on self-guided imagery in meditation (SIM). Method Following an exploratory descriptive design, we conducted qualitative interviews with 10 healthcare professionals who care for patients with mental illness and subjected the collected data to thematic content analysis. Results Participants reported that SIM had helped them to manage countertransference and had prompted changes that we categorized into three themes: managing personal vulnerability, setting clearer boundaries, and practicing self-care. Conclusion The results suggest that by cultivating wellbeing and dealing with unresolved inner conflicts, SIM can help healthcare professionals to manage countertransference.